Refractive Indices and Related Properties for Binary Mixtures of Methyl Acetate and Derivatives of Alkanolamines at Temperature Ranging from 293.15 to 313.15 K. (1st April 2021) - Hyder, M. K. Mohammad Ziaul; Akhtar, Shamim
Abstract : Refractive indices, n D, of two binary liquid systems of methyl acetate (MAc) + methylethanolamine (MEA), and MAc + dimethylethanolamine (DMEA) each at twenty-one different compositions at T = 293.15, 303.15 and 313.15 K under ambient pressure are reported. The effect of temperature on the n D values is relatively small and the higher the temperature, the lower the refractive index. From the n D data, deviation in refractive indices, Δ n D, molar refraction, R m, as well as deviation in molar refractions, Δ R m are estimated. The Δ n D and Δ R m were correlated with the Redlich–Kister equation. For each system, as a function of composition of alkanolamines, x 2, the Δ n D form a single positive lobe with a maximum between 0.5 and 0.65 mole fraction of alkanolamine. The Δ R m for both the systems are positive, the maxima lying within x 2 = 0.3 to 0.5.